Are deprivation-specific cancer survival patterns similar according to individual-based and area-based measures? A cohort study of patients diagnosed with five malignancies in England and Wales, 2008–2016 - Lucy Elliss-Brookes; Aurélien Belot; Matthew Baker; Fiona C Ingleby; Laura M Woods; Iain M Atherton (BMJ Open)
Objective To investigate if measured inequalities in cancer survival differ when using individual-based (‘person’) compared with area-based (‘place’) measures of deprivation for three socioeconomic dimensions: income, deprivation and occupation.Design Cohort study.Setting Data from the Office for National Statistics Longitudinal Study of England and Wales, UK, linked to the National Cancer Registration Database.Participants Patients diagnosed with cancers of the colorectum, breast, prostate, bladder or with non-Hodgkin’s lymphoma during the period 2008–2016.Primary and secondary outcome measures Differentials in net survival between groups defined by individual wage, occupation and education compared with those obtained from corresponding area-level metrics using the English and Welsh Indices of Multiple Deprivation.Results Survival was negatively associated with area-based deprivation irrespective of the type analysed, although a trend from least to most deprived was not always observed. Socioeconomic differences were present according to individually-measured socioeconomic groups although there was an absence of a consistent ‘gradient’ in survival. The magnitude of differentials was similar for area-based and individually-derived measures of deprivation, which was unexpected.Conclusion These unique data suggest that the socioeconomic influence of ‘person’ is different to that of ‘place’ with respect to cancer outcomes. This has implications for health policy aimed at reducing inequalities. Further research could consider the separate and additional influence of area-based deprivation over individual-level characteristics (contextual effects) as well as investigate the geographic, socioeconomic and healthcare-related characteristics of areas with poor outcomes in order to inform policy intervention.